Learning Alphabets Through Infographics - ODEWUMI, MICHAEL OLUBUNMI; OPUTA, Grace O, Grace O.; BELLO, Isyaka (Universitas Negeri Makassar, 2020)
Early stages of reading and writing rest solely on the alphabet.Â Learning of letters with infographics in the elementary classes makes learning more easy and meaningful.Â The study examined the potentials of infographics in enhancing learning at an early childhood level especially on letters.Â The researcher utilized experimental design which including pre and post-test. The package was validated by experts with a reliability coefficient of 0. 77. The findings of this study showed that the experimental group means a score of 30.60 is higher than the control group means a score of 30.50 co-efficient. Moreover, the means score of 30.742 for females and 30.345 for male pupils was obtained. The study concluded that children at the early childhood level could learn better using infographics based approach. It was recommended that incentives should be provided for pre-school teachers to participate in highly effective staff development to help them integrate infographics into their teaching and learning. Also, infographics based approach be used for all subjects in early childhood education in Nigeria